An adaptive analytical approach for lean and green framework - Leong, Wei Dong (2021)
The recent global supply chain has exposed the industrialists in a tough position when dealing with uncertain global issues such as political changes, fluctuation on foreign exchange, raw material supplies and recession. As these challenges are inevitable, the industrialists constantly seek for alternative solutions to stay competitive in the market. The recent advancement in Industry Revolution 4.0 (IR4.0) can bring many advantages and benefits to the industrialist. As new technology required high investment cost and development of new talent, many industrialists are not confident in investing in the technology especially during the bad economy time. Therefore, the development of adaptive lean and green (L&G) framework is to build the industrialist’s confident with the elements of IR4.0 to enhance operational and environmental performance while transitioning the industry towards IR4.0. Based on the real-time condition, the L&G model incorporates both quantitative and qualitative data input for both process improvement and de-bottlenecking. The model emphasized on a data-driven approach to address process optimization and debottlenecking challenges. Industry case studies are used to demonstrate the application of the developed model in each chapter. The L&G framework has reflected an improvement of 18.25% in process improvement. Meanwhile, the debottlenecking strategy reflects the possible pathways with the consideration of operation, economic and environment to enable the industrialist to be flexible and adaptive towards the uncertainty in the global economy. The performance of the L&G model is highlighted at the end of each chapter.